2018
DOI: 10.1007/s13193-018-0841-8
|View full text |Cite
|
Sign up to set email alerts
|

CR-Possum—Can It Be Used to Predict Morbidity? A Single-Centre Retrospective Study

Abstract: Preoperative prediction of morbidity in colorectal cancer (CRC) surgery helps to optimize the surgical outcome. In this study, we aim to develop a dedicated equation for predicting operative morbidity using colorectal possum scoring system and also to validate the predictive accuracy of CR-POSSUM scoring system in prognosticating actual complications. We did a retrospective analysis of 322 patients undergoing colorectal cancer surgery from a single centre in South India from 2004 to 2016. Mortality and morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…As shown in our study, the NSQIP model has an AUC of 0.72 and a Codman score of 0.68. Both of these are similar to previous morbidity prediction tools studied in colorectal cancer populations, including the CR-POSSUM (AUC = 0.716), the SURPAS (AUC = 0.66) and the Surgical Apgar Score and American Society of Anesthesiologists physical status classification (AUC = 0.6-0.77) [16,17]. The advantage of the Codman score compared to these alternative models is the relative ease of data collection.…”
Section: Use Of the Resultant Data To Identify All Predictors Of In-h...supporting
confidence: 66%
“…As shown in our study, the NSQIP model has an AUC of 0.72 and a Codman score of 0.68. Both of these are similar to previous morbidity prediction tools studied in colorectal cancer populations, including the CR-POSSUM (AUC = 0.716), the SURPAS (AUC = 0.66) and the Surgical Apgar Score and American Society of Anesthesiologists physical status classification (AUC = 0.6-0.77) [16,17]. The advantage of the Codman score compared to these alternative models is the relative ease of data collection.…”
Section: Use Of the Resultant Data To Identify All Predictors Of In-h...supporting
confidence: 66%
“…The P-POSSUM scale was created in order to correct the elevated mortality risk obtained by POSSUM [3]; some studies showed an increased accuracy of P-POS-SUM over POSSUM in mortality prediction, with near results with the observed mortality [9][10][11][12]16]. Given that P-POSSUM has to be correlated to the general condition of the local population for it to be effective [9][10][11][12][13], variability of results obtained is explained by lack of adjustments to population baseline characteristics that generate changes in predicted values. Among these characteristics are malnutrition and economic status; nevertheless literature, as our study, reports P-POSSUM scale has an increased accuracy to predict mortality compared with POSSUM in emergency surgery [12].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mortality, both Raut et al and Mohammed et al proved the accuracy of POSSUM and P-POSSUM scores in predicting mortality risk, with more than 80% of accuracy in selected patients [ 9 , 10 ]. Additionally, Prabakaran et al found that selected colorectal surgery patients have an increased prediction force, for that reason a subclass of POSSUM (CR-POSSUM) has been described in these populations [ 11 ]. Nevertheless, it has been described that score results shouldn’t be generalized to all patients that underwent surgical procedures and have to be personalized and analyzed according to each population [ 12 ].…”
Section: Introductionmentioning
confidence: 99%